On the robustness of ultra-high voltage 4H-SiC IGBTs with an optimized retrograde p-well - Tiwari, Amit K.; Perkins, Samuel; Lophitis, Neophytos; Antoniou, M.; Trajkovic, T.; Udrea, F. (My University, 2019)
The robustness of ultra-high voltage (>10kV) SiC IGBTs comprising of an optimized retrograde p-well is investigated. Under extensive TCAD simulations, we show that in addition to offering a robust control on threshold voltage and eliminating punch-through, the retrograde is highly effective in terms of reducing the stress on the gate oxide of ultra-high voltage SiC IGBTs. We show that a 10 kV SiC IGBT comprising of the retrograde p-well exhibits a much-reduced peak electric field in the gate oxide when compared with the counterpart comprising of a conventional p-well. Using an optimized retrograde p-well with depth as shallow as 1 μm, the peak electric field in the gate oxide of a 10kV rated SiC IGBT can be reduced to below 2 MV.cm-1, a prerequisite to achieve a high-degree of reliability in high-voltage power devices. We therefore propose that the retrograde p-well is highly promising for the development of>10kV SiC IGBTs.
Keywords: Oxide breakdown; Punch-through; Retrograde p-well; SiC IGBT; Threshold voltage; Ultra-high voltage